The New Method of Analyzing the Continuous Curved Flat Bar Subject To Space Load - Nguyen, Hong Son; Trung Le, Dung Bao; Tran, Van Quan; Nguyen, Quang Hung (International journal of recent technology and engineering, 2019)
The report presents a new method for linear analysis of continuous curved flat bar, subject to any load in space. This method is a combination of improving the expression of the load and displacement at the two ends of the curved bar element of the Transfer Matrix Method and Finite Element Method (TMMFEM), called the Matrix Method transfer improvements. The research results are to build math problems and programming with Matlab, verify with the results according to SAP2000 oftware and « Strength of materials » documents.